Innovative Information Systems Modelling Techniques - Kalloniatis, Christos (IntechOpen, 2012)
The rapid development of new Information Infrastructure combined with the increased user needs in specific areas of Information Technology (mostly related to Web applications) has created the need for designing new modeling techniques more innovative and targeted on specific areas of Information Systems in order to successfully model the rapidly changed environment, along with the newly introduced concepts and user requirements. Therefore, this book aims to introduce readers to a number of innovative Information modeling techniques. It is titled "Innovative Information Systems Modelling Techniques" and includes 9 chapters. The focus is on the exploration and coverage of the innovations of recently presented modeling techniques and their applicability on the Information Systems' modeling.